Church and State Relations in the Constitution of Malta - Kevin Aquilina (Polonia Sacra)
This paper discussed the relationship between the Catholic Church and the State of Malta as evidenced primarily in the Constitution of Malta and secondarily in other Constitutional Laws. It is noted that the Roman Catholic Apostolic Religion is the national religion of Malta. Malta is a confessional state which respects freedom of conscious and worship and all other religions and cults are protected by law. It considers other instances, such as the instructions of children in state schools in the Catholic religion and the influence of the Catholic Church on the state. However, lately, the relationship between the Church and the State has suffered as the state is becoming more liberal in orientation as evidenced by the enactment of laws which do not comply with the Catholic teaching of the Church’s magisterium. Hence, this opens different challenges to the Catholic Church in Malta not hitherto known to it.